An unrecognized key population? Traditional treatment practices associated with HIV risk among traditional healers in rural South Africa. (1st December 2020) - Audet, Carolyn M.; Ngobeni, Sizzy; Mkansi, Mevian; Wafawanaka, Floidy; Aliyu, Muktar H.; Vermund, Sten H.; Wagner, Ryan G.
Abstract : Objective: To understand the risk of HIV acquisition through occupational exposure among rural South African traditional healers, notably via the practice of traditional skin incisions with razors. Design: A random sample of traditional healers living in South Africa participated in a cross-sectional survey that included a rapid HIV test. Setting: Rural Bushbuckridge district of Mpumalanga, South Africa. Participants: Traditional healers. Intervention: Pretest counseling, posttest counseling, and referral to care if HIV seropositive. Main outcome measure(s): HIV infection. Results: Among healers who reported a previous positive test result or accepted an HIV test (96%), HIV prevalence was 30% (95% confidence interval: 23–37%). During their careers, 98% of healers reported conducting at least one 'vaccination' (as traditional incisions are called), 32% reported always using gloves when conducting these procedures, 29 (14%) reported patient blood touching their bare skin. Healers who reported exposure to patient blood had a higher HIV prevalence than their nonexposed colleagues (adjusted risk ratio: 2.35, 95% confidence interval: 1.55–3.56, P = 0.001). Conclusion: Nearly all traditional healers are routinely performing minimally invasive skin incisions that could expose them to patient blood. The lack of training and access to personal protective equipment increase their risk of acquisition of blood–borne pathogens, including HIV. Given the widespread practice of traditional skin incisions across southern Africa, and the higher levels of HIV among traditional healers exposed to patient blood, it is likely that traditional healers are a hitherto unrecognized key population at disproportionate risk of acquiring HIV. Abstract : Supplemental Digital Content is available in the text